2007
DOI: 10.1590/s1679-87592007000200003
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton assemblages from a tidal channel in the Bahía Blanca Estuary, Argentina

Abstract: In this study we investigate for the first time the zooplankton assemblages in a relatively small tidal channel called Bahía del Medio, situated in the middle-outer area of the Bahía Blanca Estuary, South of the Main channel. We focused the study on micro- and mesozooplankton assemblages with emphasis on tintinnids, copepods and meroplankton along the annual cycle 1997-1998. Fifteen species of tintinnids belonging to 6 genera were observed in the study area, the mean total tintinnid abundance fluctuating betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In the Americas there are few records of Monstrilloida from high latitudes of the Southern hemisphere (i.e. Ramírez, 1971;Marín and Antezana, 1985;Dias, 2005;Suárez-Morales et al, 2006;Dias and Bonecker, 2007a, b;Biancalana et al, 2007;Hoffmeyer and Barría de Cao, 2007), and only two species have been hitherto reported from Subantarctic waters (Razouls, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Americas there are few records of Monstrilloida from high latitudes of the Southern hemisphere (i.e. Ramírez, 1971;Marín and Antezana, 1985;Dias, 2005;Suárez-Morales et al, 2006;Dias and Bonecker, 2007a, b;Biancalana et al, 2007;Hoffmeyer and Barría de Cao, 2007), and only two species have been hitherto reported from Subantarctic waters (Razouls, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In Bahia Blanca, Argentina, at the same general latitude range (42°S), records include Monstrilla sp., M. helgolandica, and M. aff. serricornis (Hoffmeyer and Barría de Cao, 2007). It is not explicitly stated if the latter records are from females or males, but it is probable that the females were identifi ed as M. helgolandica following Ramírez (1971) and the males as M. aff.…”
mentioning
confidence: 99%
“…In addition, a negative correlation between the number of individuals and salinity was determined (p < 0.05). Other studies have reported that tintinnid species and number of individuals have a negative correlation with salinity (Capriulo and Carpenter, 1983;Kamiyama and Tsujino, 1996;Hoffmeyer and Cao, 2007;Lee and Kim, 2010). Durmus and Balkis (2014) found similar results in their study carried out in the southeast of the Sea of Marmara, and also stated that DO is positively correlated with the number of species and individuals.…”
Section: Discussionmentioning
confidence: 89%
“…Both sites are located within tidal channels ranging 50-300 m width and 4-7 m depth. The first experiment was performed at Bahía del Medio (BM), which is not directly impacted by human stress (Baldini et al 1999, Hoffmeyer andBarría de Cao 2007), while the second experiment was conducted in Canal Vieja (CV), a site directly affected by cultural eutrophication since it receives point-source untreated domestic effluent from the adjacent Bahía Blanca city (300,000 inhab.). The experiments were daily-deployed on March 6, 2012, to match the seasonal pulse of microzooplankton (Barría de Cao et al 2011) and the first annual phytoplankton bloom (Guinder et al 2013).…”
Section: Experimental Set-up and Rate Calculationmentioning
confidence: 99%